Existential risks and problem of escapism under conditions of e-culture - Baeva, Liudmila (Przegląd Wschodnioeuropejski, 2020)
The article is devoted to the study of new existential problems of man in the conditions of electronic culture, forms of alienation from reality, virtual escapism, “being to death” in network communities of suicidal orientation, new forms of transcendence in electronic culture. The human existence under the e-culture conditions causes a shift in its main spheres (communication, creativity, education, leisure, art), forms a range of new problems both in value, ethical and ontological-existential relations. On the basis of the existential-axiological approach, it is shown how the values of the reality and game, life and death shift in the minds of young people in network communities and “death groups” in search of their own individuality and freedom from the society. It is identified that the electronic environment allows to transform communication, change the character of sociality, existence and transcendence of a person in the virtual being. The study results show that today the electronic environment has become not only a stronghold of modern communication and unprecedented integration of the society, but also a ground for deliberate and unconscious escape from the social reality, new manifestations of escapism and giving up the desire to live in the reality.